DECISION ON THE CIVIL EXCEPTION DEVIATES FROM ARTICLE 136 HIR (ANALYSIS OF THE DECISION OF PN SEMARANG NUMBER: 73/Pdt.G/2010/PN.SMG) - Mochammad Dja’is (Diponegoro Law Review, 2017)
Exceptions should be examined and decided along with the subject matter (Article 136 HIR). The Semarang District Court (PN Semarang) has cut a separate exception from the principal issue of the case. The purpose of the study to know whether exactly the decision of PN Semarang. Data were obtained through literature study and participant observation. Based on the qualitative analysis known, the decision of the exception separated from the principal case by PN Semarang is appropriate. The makers of the National Civil Law Procedure should determine, the decision of the exception is left to the judge's discretion.